Empagliflozin Protects against Haloperidol Experimentally-Induced Ovarian Toxicity - Walaa Yehia Abdelzaher; Michel De Waard; Alyaa Abdelfattah Abdelmonaem; Dalia Mohamed Ali; Nashwa Fathy Gamal El-Tahawy; Rehab Ahmed Rifaai; Hatem A. Mohamed; Kareem Shaheen; Mohamed Ahmed Zeen El-Din; Nermeen N. Welson; Shereen ELsayed Tawfeek; Gaber El-Saber Batiha; et al. (MDPI AG, 2023)
The present experiment aimed to identify the potential protective role of empagliflozin (EMPA) on haloperidol (HAL)-induced ovarian damage in female rats because of its anti-inflammatory, antioxidant, and antiapoptotic effects. EMPA was administered in the presence and absence of HAL. Thirty-two adult female albino rats were divided into four groups. Control group, EMPA group: received EMPA (10 mg/kg/day) p.o., HAL group: received HAL (2 mg/kg/day) p.o., HAL + EMPA group: HAL (2 mg/kg/day) combined with EMPA for 28 days. Serum follicle-stimulating hormone (FSH), luteinizing hormone (LH), and anti-mullerian hormone (AMH) levels were measured. Ovarian oxidative stress parameters, besides inflammatory and apoptotic biomarkers, and ovarian Sirtuin-1 (Sirt-1) were evaluated. Ovarian histopathological examination and heat shock protein 70 (Hsp70) immunohistochemical study were performed. HAL significantly increased serum levels of FSH, LH, and ovarian inflammatory, apoptotic, and oxidative stress biomarkers and decreased serum AMH levels and Sirt-1 expression. Histopathological findings of ovarian damage and high Hsp70 immunoexpression were detected. EMPA significantly normalized the distributed hormonal levels, oxidative stress, inflammatory, and apoptotic biomarkers with a prompt improvement in the histopathological picture and a decrease in Hsp70 immunoexpression. Accordingly, EMPA protected against HAL-induced ovarian toxicity by modulating the Sirt-1/Hsp70/TNF-α/caspase-3 signaling pathway.